CREATIVE APPROACHES TO THE TEACHING SOCIOHUMANITARIAN DISCIPLINES, IN THE TRAINING OF GENERATION "Z" REPRESENTATIVES - Tatiana Kadlubovich; Darina Chernyak ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The article deals with the value orientations, attitudes, life views of modern students - representatives of Generation "Z", for whom digital technologies are an everyday reality. The experience of working with students during class and independent work is given. The authors, based on the latest research, prove that the modern generation with its peculiarities needs new creative methods and teaching methods that will take into account the specifics of cognitive activity of modern youth, its values, needs, psychological characteristics and technical skills. It is necessary to change not only teaching and learning methods, but also the style of communication between the subjects of the educational process, the form of presentation of information, knowledge, preparation of a new type of educational and methodical literature, active use of information and communication technologies.